Novel approach for optimization of fermentative condition for polyhydroxybutyrate (PHB) production by Alcaligenes sp. using Taguchi (DOE) methodology - Tripathi A.D.; Srivastava S.K. (My University, 2025)
Polyhydroxybutyrate (PHB) is a biodegradable thermoplastic polymer which is accumulated as energy reserve material by large number of microorganisms including bacteria, fungus and yeast under nutrient stress condition. In this study, efforts have been made to optimize PHB production by Alcaligenes sp. NCIM 5085 using Taguchi (DOE) methodology. This approach facilitates the study of interaction of a large number of variables spanned by factors and their settings with a smaller number of experiments, leading to considerable savings in time and cost for process optimization. Eight factors at two levels with an OA layout of L-12 were selected for proposed experimental design. PHB concentration was increased from 5.20 to 6.58 g/L under optimal cultural condition. Result validation showed 95% resemblance with the expected value. © 2011 Academic Journals.